1992
DOI: 10.1128/iai.60.9.3704-3713.1992
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi HSP70 homolog: characterization of an immunoreactive stress protein

Abstract: The gene encoding an immunoreactive Borrelia burgdorferi HSP70 homolog was isolated and characterized. The predicted amino acid sequence of this spirochetal protein confirms that this gene encodes a member of the HSP70 family of proteins. Although there appears to be a single copy of this gene on the spirochetal chromosome, two distinct transcripts hybridizing to the hsp70 probe are detected in RNA isolated from B. burgdorferi. The amount of spirochetal HSP70 RNA transcripts is shown to be thermally regulated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…1). The cloned sequence shows two differences, C3T at position 140 (Anzola 1158) and A3G at position 446 (Anzola 1525), from the HSP70 sequence previously reported (3). The nucleotide change at position 140 results in a Glu3Ile change.…”
Section: B Burgdorferi Ten Isolates Of B Burgdorferimentioning
confidence: 60%
See 1 more Smart Citation
“…1). The cloned sequence shows two differences, C3T at position 140 (Anzola 1158) and A3G at position 446 (Anzola 1525), from the HSP70 sequence previously reported (3). The nucleotide change at position 140 results in a Glu3Ile change.…”
Section: B Burgdorferi Ten Isolates Of B Burgdorferimentioning
confidence: 60%
“…Evidence in support of this is that (i) there is no evidence that directly links the immune response to B. burgdorferi HSP70 with human inflammatory disease (3), (ii) antibodies directed against B. burgdorferi HSP70 from three human patients failed to bind to the human HSP70 homolog (3), (iii) serum from dogs with immunologically mediated diseases failed to react with B. burgdorferi HSP70 (unpublished data), and (iv) HSP70reactive antibodies in other infectious diseases appear to recognize primarily epitopes that are not found on the homologous host protein (16). Further, Anzola et al (3) found that this protein sequence failed to react with human lymphocytes from three patients, indicating that this protein is not associated with arthritis in humans. The possible role of cell-mediated immunity against the Borrelia HSP70 protein in an autoimmune response is unknown.…”
Section: B Burgdorferi Ten Isolates Of B Burgdorferimentioning
confidence: 99%
“…The 80-kDa band was isolated from the gel and used for amino-terminal peptide sequencing by high performance liquid chromatography, which revealed that this antigen is a member of the HSP family ( Table 1). The aoHGE HSP-70 sequence shows substantial homology to the reported sequence of B. burgdorferi HSP-70 (1).…”
mentioning
confidence: 71%
“…the interest of microbiologists for many years, since they represent major targets of the host's immune response (19). Although less extensively studied than GroEL, DnaK homologues of many bacterial pathogens have been found to be immunogenic in humans or animals (1,2,5,8,10,47). Furthermore, as has been shown by the experimental infection of mice with Borrelia burgdorferi, immunization with proteins containing DnaK-specific sequences may protect against microbial infection (4).…”
mentioning
confidence: 99%